(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Quite a number of personnel in the Ministry of Agriculture and Rural Development, the general public and even farmers (who are the major beneficiaries of the government sub sidy program), are aware of the existence of an online system of distribution known as “Electronic wallet,” an information technology company. But this existing system does not allow proper accounting of subsidized inputs, thereby giving room for diversion of inputs and other corrupt practices and hence the need for a more robust and easy to use system. This paper proposed the frameworks of farm support application software for automated green alternative solution for farm input distribution which is a web-based open-source platform. The frameworks consist of the use-case diagram, entity relationship diagram, and system flow chart. These diagrams represent the graphical representations of the system that can easily be implemented using any suitable programming language.